Portos do Brasil: um balanço econômico e institucional em 2012 - Bezerra, Marlon de Freiras (2015)
As a starting point and main motivation the strong growth of the Brazilian international trade and the resumption of public and private investment in economic infrastructure. These factors lead us to the conclusion that the Brazilian port sector is fundamentally strategic and has undergone profound changes in their structures, given the need for modernization in the context of the new global economic reality imposed by globalization. The focus of this study focuses on recent economic developments in ports and in more detail in its laws and regulations, in order to identify potential obstacles that present themselves for investments. Therefore, addressed the current configuration of the institutional framework of the Brazilian port system, which gave the repeal of Law 8,630 / 93 (Ports Law) by the Provisional Measure No. 595 ("MP 595"), 06 December 2012, converted into so-called "new law of ports", law No. 12,815 - new regulatory framework for the sector, June 5, 2013, analyzing the main changes and consequences to public and private investment. Following it holds the effective characterization of each of the 32 ports involved with Brazil's foreign trade in 2012, generating the port ranking across six economic variables used to characterize and rank Brazilian ports are: 1. Porte; 2. Influence Area (Hinterland); 3. Participation in International Trade; 4. Products Busiest by Economic Sectors; 5. Field National Work, Regional or Local; 6. Value-added of Eastern Busiest producer. Thus, it was possible to capture more properly the weight that each economic variable has for each port individually, and its relevance to the national port ranking as a whole